A Selective Release System Based on Dual‐Drug‐Loaded Mesoporous Silica for Nanoparticle‐Assisted Combination Therapy. Issue 25 (23rd May 2014) - Wang, Wenqian; Wen, Yongqiang; Xu, Liping; Du, Hongwu; Zhou, Yabin; Zhang, Xueji
Abstract A selective release system was demonstrated with a dual‐cargo loaded MSNs. When stimulated by different signals (UV or H+), this system could selectively release different kinds of cargoes individually. Furthermore, this system has been used to provide a combination of chemotherapy and biotherapy for cancer treatment. This controlled release system could be an important step in the development of more effective and sophisticated nanomedicine and nanodevices, due to the possibility of selective release of a complex multi‐drug.